Response of wheat plants (Triticum aestivum L) to stress and synthetic elicitors of systemic acquired resistance as expressed by phenolic levels in foliage and mature grain - Ramos, Oscar F. (Kansas State University, 2016)
Producers of whole wheat products are interested in marketing the health-promoting benefits of wheat antioxidants. However, they need a steady crop supply with consistent levels of antioxidants. The variable phenolic content in wheat crops is a problem. The objectives of this research were to 1) identify the factor (s) that contribute the most to the variability in phenolic content, 2) understand the mechanism (s) responsible for phenolic synthesis, and 3) artificially trigger that mechanism (s). Phenolics are hypothesized to be part of the defense response of hard red winter wheat (Triticum aestivum L) to stress. The effect of insect feeding, pathogen infection, and heat stress on phenolics in grains from wheat plants cv. Karl 92 was evaluated. Bird-cherry oat aphid (Rhopalosiphum padi) feeding stress significantly explained the variation in phenolic content. Furthermore, the relative allocation of carbon resources to grain yield/phenolic content was influenced by the stage of the plant at which aphid feeding started to occur. Based on these findings, phenolics were hypothesized to be an active defense response acting through a mechanism known as systemic acquired resistance (SAR). In order to prove this hypothesis, several synthetic elicitors of SAR were tested for their effectiveness at inducing de novo phenolic synthesis in wheat foliage and in mature grains. Elicitors that acted through the salicylic- and jasmonic acid signaling pathways were effective at inducing phenolic synthesis by 49% and 177%, respectively, in the leaves 36 hours post spray application. They also elicited a phenolic response in mature grains of up to 21% induction. Enhancement of the levels of naturally occurring phenolic compounds with antioxidant activity in wheat grains through SAR activation is a value addition strategy that can potentially increase the profitability of hard red winter wheat crops. It can also provide manufacturers of whole wheat with natural antioxidants that can potentially be used to substitute their synthetic counterparts in wheat based products.
Keywords: stress; phenolics; antioxidants; SAR; elicitorsWheat